2012
DOI: 10.1093/infdis/jis627
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Genotypes in High-Grade Cervical Lesions in the United States

Abstract: Age and racial/ethnic differences in HPV type distribution may have implications for vaccine impact and should be considered in monitoring trends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
65
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 23 publications
13
65
1
Order By: Relevance
“…All models included terms for measures previously shown to be associated with HPV 16/18, including age and diagnosis grade, thereby producing adjusted effect estimates that were controlled for potential confounding. 19 First, a full model was run that included the 2 individual and 3 area measures. Then, backward selection of variables was conducted by removing the least Original Article significant variables one at a time, and repeating this process until all variables remaining in the model were statistically significant at P < .05.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All models included terms for measures previously shown to be associated with HPV 16/18, including age and diagnosis grade, thereby producing adjusted effect estimates that were controlled for potential confounding. 19 First, a full model was run that included the 2 individual and 3 area measures. Then, backward selection of variables was conducted by removing the least Original Article significant variables one at a time, and repeating this process until all variables remaining in the model were statistically significant at P < .05.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Although reasons for the association with younger age are less clear, this finding may be related to the hypothesis that HPV 16/18-associated lesions progress more rapidly. 29 A nonavalent vaccine is currently in development that protects against additional types (HPV types 31, 33, 45, 52, and 58) and holds promise for greater protection that may provide additional benefits for the groups that are disproportionately impacted by types other than HPV 16/18 (as described elsewhere 19 ). 30,31 In the meantime, widespread vaccination programs that increase uptake and completion rates of the 3-dose series can benefit all women, including racial/ethnic minority and low-income populations who have higher cervical cancer incidence and mortality, by protecting those who would acquire infections caused by HPV 16/18.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in invasive cancers, HPV 16 and 18 are the most commonly detected types in high-grade cervical lesions; however, there is more heterogeneity in HPV type distribution in high-grade lesions. Studies have shown that HPV 16 and 18 account for a lower proportion of high-grade cervical lesions in Africa and South America compared with North America and Europe and in racial minorities in the United States (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Although currently available HPV vaccines have shown some cross-protective efficacy against nonvaccine oncogenic types (13-15), a substantial proportion of high-grade cervical lesions are caused by types against which current vaccines have not shown any degree of efficacy (11,16,17). Vaccines that target a wider array of oncogenic HPV types such as a candidate vaccine against 6/11/16/18 and 5 additional oncogenic types (31/33/45/52/58) could provide additional protection against precancerous lesions that require treatment.…”
Section: Introductionmentioning
confidence: 99%